Comparing Sleep Disorders, Procrastination, and Cognitive Intelligence in Male and Female Upper Secondary Students in Rudsar - Dehghan Rudsari, Farima; Asmaee Majd, Sirvan (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective:  This study aimed to compare sleep disorders, procrastination, and cognitive intelligence among male and female upper secondary students in Rudsar.Methods and Materials: This descriptive-analytical causal-comparative study was conducted on 400 upper secondary students, including 200 girls and 200 boys, selected through two-stage cluster random sampling from a population of 1,958 students in Rudsar during the 2024–2025 academic year. Data were collected using the Lynch et al. Sleep Disorders Questionnaire, Lay’s Procrastination Scale, and Raven’s Progressive Matrices. Data were analyzed using SPSS-26 through descriptive statistics, Levene’s test, multivariate and univariate analysis of variance, and Mann–Whitney and Wilcoxon tests for cognitive intelligence due to non-normal distribution.Findings: The multivariate analysis showed a significant overall difference between male and female students across the studied variables (Wilks’ Lambda = 0.710, F = 26.730, p < 0.001, η² = 0.290). Significant gender differences were found in sleep disorders (F = 30.54, p = 0.04, η² = 0.071) and cognitive intelligence (p = 0.002). Girls obtained higher mean scores than boys in both sleep disorders and cognitive intelligence. However, no significant difference was observed between the two groups in procrastination (F = 0.437, p = 0.509, η² = 0.001), although boys had a slightly higher mean procrastination score.Conclusion: The findings indicate that gender is associated with significant differences in sleep disorders and cognitive intelligence among upper secondary students, while procrastination does not differ significantly between girls and boys. These results highlight the need for gender-sensitive school-based screening and intervention programs targeting sleep health and cognitive-academic functioning.